2021
DOI: 10.1063/5.0058904
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of plasma–surface interaction—General picture and a case study of Si and SiO2 etching by fluorocarbon-based plasmas

Abstract: The physics and chemistry of plasma-surface interaction is a broad domain relevant to various applications and several natural processes, including plasma etching for microelectronics fabrication, plasma deposition, surface functionalization, nanomaterial synthesis, fusion reactors, and some astrophysical and meteorological phenomena. Due to their complex nature, each of these processes are generally investigated in separate subdomains, which are considered to have their own theoretical, modeling and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 298 publications
2
18
0
Order By: Relevance
“…Low-temperature plasmas are known to modify material surfaces by providing reactive and energetic gaseous species. This principle is widely applied in plasma etching, deposition, surface functionalisation and heterogeneous surface chemistry in general [1][2][3][4][5]. However, surface kinetics also affects the densities of active gaseous species in while they are predominantly lost by surface recombination back into O 2 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature plasmas are known to modify material surfaces by providing reactive and energetic gaseous species. This principle is widely applied in plasma etching, deposition, surface functionalisation and heterogeneous surface chemistry in general [1][2][3][4][5]. However, surface kinetics also affects the densities of active gaseous species in while they are predominantly lost by surface recombination back into O 2 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[174][175][176][177][178] Vanraes reviewed the standardized computational methods to be used for multiscale modeling in a case study of Si and SiO 2 etching by fluorocarbon plasmas. 179) In plasma film deposition, Depoh et al reported plasma and feature profile simulations of plasma-enhanced chemical vapor deposition (PECVD) of a titanium film. 180) Numerical simulations were also performed for physical vapor deposition (PVD), such as ionized magnetron sputter deposition.…”
Section: Sa0803-11mentioning
confidence: 99%
“…Plasma sheath models have also been reviewed shortly in one of our earlier publication [18]. In general, plasma sheath has been modeled using various techniques including mesoscopic numerical models or (semi-) analytical models.…”
Section: Previous Computational Modelsmentioning
confidence: 99%